Beyond power asymmetry: The Shimen system as relational scaffolding for international doctoral students’ collective academic identity in China - Huang, Yu; Bano, Shamillah; Shi, Anding; Wang, Zining; Jing, Xiaoli (Journal of International Students, 2026)
Existing research on cross-cultural doctoral supervision often prioritizes power asymmetries over supportive dynamics. This study examines China's Shimen system—a Confucian-rooted academic lineage—as a relational framework for international doctoral supervision. Using a phenomenological approach and semistructured interviews with 28 international doctoral students at Chinese universities, this research explores their lived experiences. The results show that Shimen serves as "relational scaffolding," offering academic guidance, emotional support, and a sense of collective belonging. This harmony-oriented structure effectively prevents identity alienation and fosters a collective academic identity. The findings challenge Western individualistic models by demonstrating how hierarchy and collectivism can serve as ethical support mechanisms. Ultimately, this study offers an indigenous theoretical framework and practical implications for developing inclusive, culturally informed supervisory practices in global higher education.